2022
DOI: 10.55493/5002.v12i11.4635
|View full text |Cite
|
Sign up to set email alerts
|

Worker Transition Across Formal and Informal Sectors: A Panel Data Analysis in Indonesia

Abstract: This paper examines the transition of workers between formal and informal jobs based on socio-demographic and employment characteristics. The study identifies factors that increase the likelihood of workers remaining in formal employment. The multinomial logistic regression model is incorporated to analyze labor transitions based on data from Indonesia's National Labor Force Survey (Sakernas) of 2017–2018. The findings show that 56.34% of workers were in informal activities and 30.58% were in formal jobs. Work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Age also influences the probability of transitioning to self-employment; Cea and Contreras (2008) showed that, in Chile, age has a positive and decreasing impact. Consistent with these results, various studies show that younger workers generally shift more frequently than older ones from the formal to the informal sector (Borjas, 2013;Ehrenberg and Robert, 2012;Sugiharti et al 2022), although this seems to be associated with the more general characteristics of younger persons of having larger labor mobility than older persons.…”
Section: Empirical Analyses On the Drivers To Informalitymentioning
confidence: 58%
See 1 more Smart Citation
“…Age also influences the probability of transitioning to self-employment; Cea and Contreras (2008) showed that, in Chile, age has a positive and decreasing impact. Consistent with these results, various studies show that younger workers generally shift more frequently than older ones from the formal to the informal sector (Borjas, 2013;Ehrenberg and Robert, 2012;Sugiharti et al 2022), although this seems to be associated with the more general characteristics of younger persons of having larger labor mobility than older persons.…”
Section: Empirical Analyses On the Drivers To Informalitymentioning
confidence: 58%
“…For Indonesia, Sugiharti et al (2022) found that experienced workers tend to transition into formal and informal jobs more than workers with no employment experience. Skill has also proved to be a relevant variable; Delaporte and Peña (2023) show that workers in routine manual formal employment in Chile become increasingly unemployed or use informality as a buffer against job losses.…”
Section: Empirical Analyses On the Drivers To Informalitymentioning
confidence: 99%